Peran Identitas Wanita Perawat dalam Memilih Keluarga - Ainul Mardiyah; Evi Yuliani; Sakhi Nabila Al Husna (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This article explores the transformation of career women's social identity after marriage through the lens of role theory in social psychology. It focuses on a former nurse who transitioned into a full-time housewife and home-based entrepreneur. Using a qualitative case study approach through in-depth interviews, the study reveals that social role transformation is influenced by internal factors such as exhaustion and emotional needs, and external factors such as social expectations and job instability. The adaptation process was gradual, with past identities continuing to influence new roles. This study highlights that women's social identity is dynamic and evolves with life context.